Search for the semi-muonic charmonium decay J/ψ → D − μ + ν μ + c. c - Ablikim, M; Achasov, MN; Adlarson, P; Ai, XC; Aliberti, R; Amoroso, A; An, MR; An, Q; Bai, Y; Bakina, O; Balossino, I; Ban, Y; et al. (Springer, 2024)
Using (10087 ± 44) × 106J/ψ events collected with the BESIII detector at the BEPCII e+e− storage ring at the center-of-mass energy of s = 3.097 GeV, we present a search for the rare semi-muonic charmonium decay J/ψ → D−μ+νμ + c.c.. Since no significant signal is observed, we set an upper limit of the branching fraction to be B (J/ψ → D−μ+νμ + c.c.) < 5.6 × 10−7 at 90% confidence level. This is the first search for the weak decay of charmonium with a muon in the final state.